The role of light, temperature and wine bottle colour on pigment enhancement in white wine - Daniel Dias; Trevor Smith; Kenneth Ghiggino; Geoffrey Scollary (2012)
Pigmentation enhancement in a Chardonnay wine with high flavan-3-ol concentration was examined by irradiating the wine under controlled conditions. Heating the wine in darkness required temperatures in excess of 50 °C before enhanced pigmentation became apparent. It was found that ultraviolet and, to a lesser extent, low wavelength visible light contributed to pigment production. The development of pigmentation depended on wine bottle glass colour: Flint > Arctic Blue > French Green > Antique Green. This is in agreement with the transmission characteristics of the bottles with even the darkest (Antique Green) allowing the transmission of some ultraviolet light. Riboflavin, when added to the wine, degraded rapidly when exposed to radiation <400 nm. The degradation of riboflavin and the onset of colour development depended on the actual amounts as well as the ratio of riboflavin to flavan-3-ol, suggesting that a complex series of reactions are occurring. A degradation product of riboflavin may be contributing to the increase in absorbance in the visible region observed during light exposure.